Perlindungan Hukum Bagi Konsumen Dalam Transaksi Jual Beli-Online (E-Commerce) - Sandhy, Purnomo (Sekolah Tinggi Ilmu Syariah Wal Aqidah Ash-Shofa Manonjaya, 2025)
The research focuses on legal protection for consumers in e-commerce by applying a normative juridical perspective. By analyzing various relevant library source materials, consisting of existing legal sources such as laws and regulations, decisions of judges in courts or jurisprudence, legal agreements both national and international, related literature, along with transaction data from e-commerce platforms. This research touches on several problems that users are experiencing in the e-commerce realm, including product mismatches with the initial description, dispute resolution difficulties, fraud, and also the threat of data leakage. In addition, this study explores the role of the Civil Code (KUHPerdata) and related regulations to provide a framework for the protection of consumer rights. In relation to compensation claims for default, this study shows that consumers certainly have the right guaranteed by law to obtain compensation if affected by the default of the seller. However, obstacles such as difficulties in exercising consumer rights in diverse jurisdictions continue to be a concern that needs to be addressed. This research focuses on the urgency of solutions, such as forms of cooperation between countries and alternative dispute resolution methods to strengthen protection for consumers.